2013
DOI: 10.1177/0218492312450448
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus pacemaker lead endocarditis

Abstract: A 47-year-old man who had a pacemaker implanted 2 years earlier, recently developed a fever and had been on antibiotics for 2 months. He presented with pulmonary emboli, and underwent lead extraction and emboli removal. Histopathology demonstrated Aspergillus. Amphotericin B was continued postoperatively. This rare case of pacemaker lead endocarditis suggests that vigorous medical and surgical intervention can be curative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…However, if the vegetations are larger than 1 cm, the risk of fatal embolic events during retraction is too high so that thoracotomy should be preferred. 61 Extensive surgery and complete recovery was reported by Reis et al [63] in a case report from 2005. The patient received an aortic root bioprosthesis after bacterial endocarditis, however, about 3 months after surgery he developed postoperative endocarditis due to Aspergillus, manifesting in several severe embolic events and peri-root abscess with extension of infected material to the aortic wall.…”
Section: Endocarditismentioning
confidence: 87%
See 3 more Smart Citations
“…However, if the vegetations are larger than 1 cm, the risk of fatal embolic events during retraction is too high so that thoracotomy should be preferred. 61 Extensive surgery and complete recovery was reported by Reis et al [63] in a case report from 2005. The patient received an aortic root bioprosthesis after bacterial endocarditis, however, about 3 months after surgery he developed postoperative endocarditis due to Aspergillus, manifesting in several severe embolic events and peri-root abscess with extension of infected material to the aortic wall.…”
Section: Endocarditismentioning
confidence: 87%
“…For removal ether intravascular retraction methods or thoracotomy are performed. However, if the vegetations are larger than 1 cm, the risk of fatal embolic events during retraction is too high so that thoracotomy should be preferred . Extensive surgery and complete recovery was reported by Reis et al .…”
Section: Endocarditismentioning
confidence: 94%
See 2 more Smart Citations
“…Diagnosing fungal endocarditis remains elusive because of negative blood cultures [ 13 , 14 ]. It has been reported that they are positive only in about 11% of cases [ 15 ], thus accounting for the high mortality. Once there is suspicion of Aspergillus infection , or when confirmed, immediate anti-fungal therapy should be initiated.…”
Section: Discussionmentioning
confidence: 99%